Development of Drama using Heuristic Method for MTs Mutiara Ilmu, North Sumatra, Indonesia - Risna Risna; Sutikno Sutikno; Rahmat Kartolo (International Journal of Research in Community Services, 2022)
The purpose of this study was to describe the design validation of the development of legend-based drama teaching materials using the heuristic method for class VII students of MTs Mutiara Ilmu, North Sumatra, Indonesia. The research method used in this research is the research & development method. The subject of research on product development in this study is the validator. In addition, the subjects of this study were seventh grade students of MTs Mutiara Sains.  The results of this study indicate that the design of developing legend-based drama teaching materials using the heuristic method for class VII students of MTs Mutiara Sains, starts from information related to students' descriptions in the implementation of learning in class, it is known that learning has been carried out well. However, students' responses to the material and evaluation of learning are still low. Based on the collection of information obtained, it was found that it was necessary to develop legend-based drama teaching materials using the heuristic method. The results of expert validation on the design of developing legend-based drama teaching materials using the heuristic method obtained an average validation score of 4 with good categories. Thus, it can be concluded that the legend-based drama teaching materials using the heuristic method are suitable for use by class VII students of MTs Mutiara Sains.